Analysis of the Scientific Production of Universities in Social Communication (2014 -2018) - Rios Incio, Felipe Anderson (2020)
This document analyzes the research in Social Communication during the years 2014 -2018 of undergraduate students in the city of Trujillo; In order to determine the methodological and thematic orientation, a total of 192 theses were analyzed using an analysis guide. Methodologically, the research corresponds to the positivist approach of comparative descriptive non-experimental design. The main findings in the universities are the non-evolution of undergraduate theses, following for many years with a quantitative approach, of non-experimentaldesign with a simple descriptive scope, the most worked areas being audiovisual communication, communication, design, advertising and marketing.